The Myth of Vilnius and Its Revision in the Diaries of Vincas Mykolaitis-Putinas - Žvirgždas, Manfredas (Colloquia, 2024)
One of the key figures of the Lithuanian-speaking intellectual elite, Vincas Mykolaitis-Putinas (1893–1967) formulated the programme of cultural nationalism, and he himself was inspired by the interwar political rhetoric. The “question of Vilnius”, which was instigated by the mobilised patriotic forces, was identified as crucial problem for the existance of the state. In his diaries of the 1938–1945, the writer and academician responded enthusiastically to the fulfilment of the political vision of the “eternal capital” in September of 1939. He cared for the reinforcement of ethnic Lithuanian cultural positions during the struggle of totalitarian regimes in 1940–1944. Some connotations of geopolitical imperialism can be seen in the diary, when the diarist insists on the urgent “re-Lithuanisation” of the public sphere. When in 1940 Mykolaitis-Putinas a well-acknowledged professor of literary studies, finally moved to the city, which has been so clearly visualised in the collective imagination for several decades, he familiarised himself extensively with the topography and cultural heritage of Vilnius. On the one hand, he never felt a stranger in the heterotopic territory; on the other hand, he seldom expressed tolerance towards the native inhabitants of the city. In the newly gained capital, Mykolaitis-Putinas tried to save the ethnocentric institutions of cultural memory (Institute of Lithuanian Studies, museums and archives preserving Lithuanian heritage). He supported the main Lithuanian-dominated cultural and educational institutions, such as the reformed Vilnius University, the Philharmonic, and the Academy of Sciences.